2018
DOI: 10.1093/ehjqcco/qcy046
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life in young adults with congenital heart disease

Abstract: Young adults with CHD have impaired physical HRQoL but normal mental HRQoL and PA. Lower physical exercise capacity, female sex, less social support and lower educational level predict an unfavorable quality of life and PA. This subgroup of patients should be monitored more closely and provided with special psychosocial care to improve long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
3
22
1
1
Order By: Relevance
“…The lack of correlation between other medical variables such as cyanosis, age or number of the surgeries and SHS or PeQoL has also been reported elsewhere. [44][45][46] The present study, however, found scoliosis to be the only medical parameter associated with poor quality of life. This finding seems logical because a significant scoliosis can potentially alter the respiratory capacity and thus the physical performance of the patient, and also negatively influence the patient's psychological approach to his (her) self-image.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The lack of correlation between other medical variables such as cyanosis, age or number of the surgeries and SHS or PeQoL has also been reported elsewhere. [44][45][46] The present study, however, found scoliosis to be the only medical parameter associated with poor quality of life. This finding seems logical because a significant scoliosis can potentially alter the respiratory capacity and thus the physical performance of the patient, and also negatively influence the patient's psychological approach to his (her) self-image.…”
Section: Discussioncontrasting
confidence: 69%
“…The NYHA class correlated significantly with the subjective physical health (SF-36) as previously reported. 29,44 NYHA has been controversially associated with the level of QoL. The lack of correlation between other medical variables such as cyanosis, age or number of the surgeries and SHS or PeQoL has also been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with congenital heart disease and healthy controls were recruited from a previous study on health-related quality of life in young adults with congenital heart diseases conducted in 2015 [12]. In short, 300 patients between 18 and 30 years of age without severe neurological impairments, comorbid genetic syndromes, severe psychiatric diagnoses and who were fluent in German were eligible for the study in 2015 and were approached when attending the cardiac outpatient clinic at the University Hospital Zurich, Switzerland.…”
Section: Study Design and Samplementioning
confidence: 99%
“…There is often variability in HRQoL between individuals and across time; hence, longitudinal designs are useful for understanding the variability of HRQoL trajectories and the factors associated with these trajectories. The paucity of longitudinal HRQoL data for patients with AMI11 limits the comprehensive evaluation of the burden of AMI, as well its appraisal as a potential study endpoint. The Evaluation of the Methods and Management of Acute Coronary Events (EMMACE)-3 and EMMACE-412 national longitudinal cohort studies collected data concerning AMI, comorbidities, treatments, clinical outcomes and HRQoL for patients with AMI in 77 hospitals in England between 2011 and 2015.…”
Section: Introductionmentioning
confidence: 99%